2018
DOI: 10.21608/jpp.2018.35247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decreasing Water Irrigation Quantity on Growth and productivity of Flame Seedless Grapevines in Clay Soils Conditions

Abstract: The present investigation was carried out during three successive seasons (2015, 2016 and 2017)to determine water requirement on growth, yield and fruit quality features of Flame seedless grapevines. In Aga, Dahlia Governorate, Egypt, the chosen vines were seven years old, planted in a clay soil, spaced 2.5×2 meters apart and irrigated by flood system, spur pruned, trained to the quadrilateral cordon and trellised by the pergola system. The vines were pruned during the second week of January with bud load (56 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
5
4
0
Order By: Relevance
“…These results may be due to that subsurface drip irrigation allows uniform soil moisture, minimize the evaporative loss and delivery water directly to the plant root zone which increases use efficiency (Kramer and Boyer 1995). This result agreement with Gaser et al (2018) who showed that water use efficiency (WUE)was significantly affected by different levels of irrigation in 2016 and 2017 seasons of this study. It was found that vines irrigated with 4000m3 /Fadden had significant values of this parameter followed by 4500m3 /fadden, while 5000m3 /fadden ranked the third position.…”
Section: Chemical Properties Of Berriessupporting
confidence: 93%
“…These results may be due to that subsurface drip irrigation allows uniform soil moisture, minimize the evaporative loss and delivery water directly to the plant root zone which increases use efficiency (Kramer and Boyer 1995). This result agreement with Gaser et al (2018) who showed that water use efficiency (WUE)was significantly affected by different levels of irrigation in 2016 and 2017 seasons of this study. It was found that vines irrigated with 4000m3 /Fadden had significant values of this parameter followed by 4500m3 /fadden, while 5000m3 /fadden ranked the third position.…”
Section: Chemical Properties Of Berriessupporting
confidence: 93%
“…The highest percentage of fruitful buds with SAP application may be due to the increasing water-holding capacity of the soil around the roots. These results are in somewhat agreement with those found by EL Gendy (2012) and Gaser et al (2018), who reported that water stress was effective in inducing early bud break compared to continuously well-watered vines.…”
Section: Effect Of Superabsorbent Polymer (Sap) Under Different Irrig...supporting
confidence: 93%
“…This is confirmed by Branch et al (2009), who showed that the application of SAP increases vegetative growth by increasing the soil's capacity to store water and nutrients. This result agreed with Gaser et al (2018), who reported that water stress decreased vegetative growth traits in grapevine. Additionally, the findings of our study are consistent with those of Pattanaaik et al (2015), who discovered that soil application of SAP at a concentration of 100 g/tree greatly improved the vegetative growth of Khasi mandarin compared to the control.…”
Section: Effect Of Superabsorbent Polymer (Sap) Under Different Irrig...supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those obtained by El-Morsy et al (2017), who studied the black cultivar Arra 24 and the white cultivar Arra 30, noting that these cultivars exhibited thick internodes. According to Gaser et al (2023), cultivars of starlight and sugrafourteen showed the same tendency and numerous researchers working with various cultivars Tarbia, 2017 andEl-Sayed andFayed, 2023).…”
Section: The Description Parametersmentioning
confidence: 83%